Growth dynamics of superficial roots in Portuguese plantations of Eucalyptus globulus Labill. studied with a mesh bag technique - Fabião, António (2009)
The variation in growth of the fine roots of blue gum (Eucalyptus globulus Labill. spp. globulus)in the 0-40 cm soil layer was studied from March 1982 to March 1983 at Quinta do Fradouro, Óbidos, Portugal. A mesh bag method was used; bags of nylon net were inserted into a clay soil and a sandy soil and filled with root-free soil. They were resampled after 2, 4, 6 and 12 months in both places and in a separate series in the sandy soil every second month throughout the year.